Language Choice and Attitude in Sumatran-Javanese Intermarriage Families in Relation to Language Maintenance in Lubuklinggau - Sastika Seli (Journal of English Education, Literature and Linguistics, 2020)
The purpose of this research was to find out (1 language chosen by intermarriage Sumatran-Javanese community in Lubuklinggau, (2 the language attitudes that affect language maintenance toward parents’ languages and 3) the factors that determine the language choice. It was a sociolinguistic research with descriptive qualitative method. The subject of the research was 100 people that were chosen by purposive data sampling. In collecting the data, interview and questionnaire were used by the researcher. The result showed that Palembang Malay Lubuklinggau dialect (PMLD) had highest number of speakers in family and friendship domain. Meanwhile, Indonesian language was the highest used in non-casual domain such as religion, education, employment and public domain. Due to the choice, attitude presented by the informants was negative attitude proved by the less pride, lack of awareness and lack of loyalty toward parents’ language that result the less effort to maintain parents’ first language. The factors that determine the language choice among intermarriage Sumatran-Javanese community in Lubuklinggau were were to show identity, the effect of environmental force, the effect of community and workplace force, participants and setting, topic and language status/prestige.